Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.24059/olj.v25i2.2227
|View full text |Cite
|
Sign up to set email alerts
|

Examining Students’ Online Course Perceptions and Comparing Student Performance Outcomes in Online and Face-to-Face Classrooms

Abstract: Through the use of existing grade and student survey data, this study investigated online courses offered at a public four-year university. Specifically, the study explored differences in student success rates between online and face-to-face courses for traditional undergraduate students as well as the climate of student perceptions towards online courses. Our general results suggest that students performed better in, and had higher levels of preference toward, traditional face-to-face formats. However, overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 62 publications
3
23
0
Order By: Relevance
“…For some of these students, online study came as a positive surprise; some even considered studying fully online. While the literature has reported positive experiences of online learning, it also reported that despite these positive perceptions students still have a stronger preference for face-to-face classes, e.g., [15]. The fact that some of the students considered going fully online with their education is somewhat unexpected.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For some of these students, online study came as a positive surprise; some even considered studying fully online. While the literature has reported positive experiences of online learning, it also reported that despite these positive perceptions students still have a stronger preference for face-to-face classes, e.g., [15]. The fact that some of the students considered going fully online with their education is somewhat unexpected.…”
Section: Discussionmentioning
confidence: 95%
“…As we move towards a post-pandemic environment of learning, students' preferences have shifted to blended learning so that they can benefit from the hybrid experience of a face-to-face classroom with the advantages of online learning. Whilst online education has been perceived to not be on equal standing as traditional classrooms, some students have a stronger preference for face-to-face classes even though their online experiences were also positive [15]. As we emerge from the pandemic, blended learning is considered to be effective and an accepted teaching environment that is very popular [16] and even considered as the new normal [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is also said that e-learning helps the learning process that cannot be done face-to-face. Mixing face-to-face learning and online learning will further maximize the efforts of educators as managers in achieving learning goals [31].…”
Section: Literature Review 21 the Basic Concept Of Distance Learningmentioning
confidence: 99%
“…That is, differences within the characteristics of scholars themselves may drive differences within the outcome measures we observe that are unrelated to the mode of instruction (Arias et al, 2018). Additionally, the content, instructor, assignments, and other course features might differ across online and in-person modes also, which makes apples-to-apples comparisons difficult (Spencer & Temple, 2021).…”
Section: Introductionmentioning
confidence: 99%